Soccernomics : why England lose, why Germany, Spain and France win, and why one day the rest of the world will finally catch up /: why England lose, why Germany, Spain and France win, and why one day the rest of the world will finally catch up. (2018) - Kuper, Simon; Szymanski, Stefan, 1960-
No abstract available